Population-Level Equity May Not Be Achievable At the First Level of the Iranian Family Physician Program (IFPP) - Reza Jourvand; Farkhonde Amin Shokravi (Tabriz University of Medical Sciences, 2015)
According to the current legislation and article 89 of Iran's Fourth Development Program (I4DP), the Ministry of Health and Medical Education (MOHME) is responsible for the countrywide planning of health policies. Thus, MOHME with the help of all other organizations that have direct role in provision of health care (e.g. governmental health insurance companies) started to study and compile regulations of referral system and family physi-cian program, introduced later as the "Iranian Na-tional Family Physician Program"(IFPP).